Гірнича складова епохи великих географічних відкриттів - Гайко, Геннадій Іванович; Білецький, Володимир Стефанович (Український культурологічний центр, 2015)
У статті аналізуються основні рушії епохи Великих географічних відкриттів (ВГВ), зокрема прагнення до коштовних металів Нового світу; систематизовано історичний огляд опанування мінеральних скарбів Іспанської Америки, розглянуті основні осередки видобутку золота й срібла, показана роль конкістадорів в організації гірничих робіт і доля автохтонного населення, змушеного працювати в численних рудниках, оцінене значення мінеральних ресурсів Нового світу для становлення світової фінансової системи й міжнародної торгівлі ХVI - ХVII ст.

The paper reviews the major drives of the period of great geographic discoveries, specifically aspiration for precious metals of the New World; systematizes the historical background of acquisition of the mineral wealth of Spanish America; examines the main gold and silver mining centers; shows the role of conquistadors in mining management and the share of autochthonous population who had to work in numerous mines; evaluates the significance of mineral resources of the New World for the buildup of the world financial system and international commerce in the 16th - 17th centuries. Important steps on that way were the mining colonization of the Aztec and Inca Empire by the Europeans, Peruvian gold, silver and mercury deposits. It is concluded that the colonization as well as mining and industrial development of African and American territories discovered by the Europeans determined the long-term geography of the main developments of the world amplest mineral resources.
Mining constituent of the period of great geographical discoveries
Keywords: географічні відкриття; мінеральні ресурси; історія гірництва; конкістадори; Ельдорадо; гірнича колонізація територій; освоєння надр; гірники-невільники; міжнародна торгівля; "іспанська недуга"; geographic discoveries; mineral resources; mining history; conquistadors; El Dorado; mining colonization of territories; resources development; miners-slaves; international commerce; 'Spanish ailment'